Substrate Pre-loading Influences Initial Colonization of GAC Biofilter Biofilms - Qin, Wen; Hammes, Frederik (Frontiers in Microbiology, 2021)
Microbial community composition and stability affect pollutant removal for biological/granular activated carbon (BAC/GAC) processes. Here, we pre-loaded the organic carbon substrates sucrose, lactose and LB-medium onto new GAC prior to use, then tested whether this substrate pre-loading promoted development of biofilms with high coverage that remained stable for prolonged operational periods. Temporal dynamics of the biomass and microbial community on the GAC were monitored via flow cytometry and sequencing respectively, in both batch and continuous-flow experiments. In comparison with the non-loaded GAC (control), the initial biofilm biomass on substrate loaded GAC was 3-114 times higher, but the initial richness was considerably lower (only accounting for 13-28 % of the control). The initial community compositions were significantly different between batch and continuous-flow column experiments, even when loaded with the same substrates. In the continuous-flow column experiments, both biomass and microbial community composition became remarkably similar to the control filters after 64 days of operation. From these findings, we conclude that substrate loaded GAC could enhance initial colonization, affecting both biomass and microbial community composition. However, the biomass and composition did not remain stable during long term operation due to continuous dispersal and competition from influent bacteria.